Diabetic ketoalkalosis due to ectopic ACTH production from an oat cell carcinoma. Issue 669 (July 1981) - Pearson, D. W.; Thomson, J. A.; Kennedy, A. C.; Toner, P. G.; Ratcliffe, J. G.
Abstract : A diabetic patient is described who presented with the bizarre biochemical association of hyperglycaemia, ketosis and severe alkalosis. Investigation revealed hypercortisolaemia due to ectopic adrenocorticotrophic hormone secretion from an oat cell carcinoma of the bronchus and post-mortem studies demonstrated clinically unsuspected resolving pancreatitis. a possible mechanism for the metabolic upset is discussed.